The effect of oil palm trunk filler in expoxied natural rubber - Mohd Saiful Affendi, Zabidi (2010)
The effect of loading oil palm trunk as filler in natural rubber was investigated in this research. The testing that will be made on the reinforced fiber rubber are tensile strength test and swelling test. The natural rubber is obtained from Rubber Research Institute Malaysia (RRIM). There are three types of rubber in this research. They are Epoxied Natural Rubber (ENR), Standard Malaysian Rubber (SMR), and Styrene-Butadiene Rubber (SBR). The selected ENR will be milled on the two roll mill machine and mix with filler after the milling process. The filler will be divided into five different of parts per hundred rubbers (phr). The compounds will be vulcanized with sulfur and ready to be molded. The molded rubber will be tested. The machines that will be used in this research are two roll mill for compounding and hot press machine for molding. Two roll mills will operate for 3 hours per compound. The hot press machine will be used for 25 minutes each molding sessions. Conventional filler is the carbon black filler. Oil palm trunk is used as filler to compare with carbon black filler in terms of rubber properties. It was found out that the higher the amount of oil palm trunk in rubber, the lower the tensile strength of the rubber. The swelling of rubber product is higher in kerosene compare with diesel. When the filler content increase, the mixing time will be increased